Serum amyloid P-component and C-reactive protein in serum of healthy Icelanders and members of an Icelandic family with macroglobulinaemia. - Jensson, O; Björnsson, OG; Arnason, A; Birgisdóttir, B; Pepys, MB (1982)
Serum levels of amyloid P-component (SAP) and C-reactive protein (CRP) were determined in 260 asymptomatic Icelanders of both sexes and various age groups and in 60 members of a family with macroglobulinaemia. In the normal group the SAP levels were normally distributed but slightly higher than in a comparable British group. Elevated levels of SAP and CRP were found in four elderly sibs of the macroglobulinaemia family. Two of them had benign monoclonal macroglobulinaemia (BMM), one had Waldenström's macroglobulinaemia and one increased polyclonal IgA. In addition, a notable small increase (2-20 micrograms/ml) in the levels of CRP was found in 6 children and 3 grandchildren of two elderly sibs with BMM. This increase in serum CRP levels was also found in five of six family members when investigated four years later. The HLA haplotypes present in the family members, including B7, are not closely associated with the various abnormal protein changes detected in the elderly sibs of the second generation or their descendents. Likewise, the increased levels of SAP, CRP or IgM are not associated with any particularly type of the genetic protein markers of blood group systems tested.